Patterning of human epidermal stem cells on undulating elastomer substrates reflects differences in cell stiffness. (15th March 2019) - Mobasseri, Seyedeh Atefeh; Zijl, Sebastiaan; Salameti, Vasiliki; Walko, Gernot; Stannard, Andrew; Garcia-Manyes, Sergi; Watt, Fiona M.
Graphical abstract: Abstract: In human skin the junction between epidermis and dermis undulates, the width and depth of the undulations varying with age and disease. When primary human epidermal keratinocytes are seeded on collagen-coated polydimethylsiloxane (PDMS) elastomer substrates that mimic the epidermal-dermal interface, the stem cells become patterned by 24 h, resembling their organisation in living skin. We found that cell density and nuclear height were higher at the base than the tips of the PDMS features. Cells on the tips not only expressed higher levels of the stem cell marker β1 integrin but also had elevated E-cadherin, Desmoglein 3 and F-actin than cells at the base. In contrast, levels of the transcriptional cofactor MAL were higher at the base. AFM measurements established that the Young's modulus of cells on the tips was lower than on the base or cells on flat substrates. The differences in cell stiffness were dependent on Rho kinase activity and intercellular adhesion. On flat substrates the Young's modulus of calcium-dependent intercellular junctions was higher than that of the cell body, again dependent on Rho kinase. Cell patterning was influenced by the angle of the slope on undulating substrates. Our observations are consistent with the concept that epidermal stem cell patterning is dependent on mechanical forces exerted at intercellular junctions in response to undulations in the epidermal-dermal interface. Statement of significance: In human skin the epidermal-dermal junction undulates and epidermal stem cells are patterned according to their position. We previously created collagen-coated polydimethylsiloxane (PDMS) elastomer substrates that mimic the undulations and provide sufficient topographical information for stem cells to cluster on the tips. Here we show that the stiffness of cells on the tips is lower than cells on the base. The differences in cell stiffness depend on Rho kinase activity and intercellular adhesion. We propose that epidermal stem cell patterning is determined by mechanical forces exerted at intercellular junctions in response to the slope of the undulations.